Tipología de ciudadanos frente al soborno policial para el ámbito peruano - Olazabal Tamayo, Maria Alejandra (2021)
Latent class analysis (LCA) based on the Tenth National Survey on Corruption Perceptions carried out by Proética in 2017. The parametric method used allows demonstrating the heterogeneity of the agents that fall into acts of micro corruption (bribery) in the Peruvian environment thanks to three underlying unobserved categorical variables (tolerance, victimization and propensity) and four control variables (socioeconomic level and gender). It is concluded that it is possible to construct a typology that allows profiles to be established according to tolerance, victimization and propensity.